The Restorative Justice: Ideality, Reality, and Problems in The Indonesia Criminal Justice System: Restorative Justice: Idealita, Realita, dan Problematika dalam Sistem Peradilan Pidana di Indonesia - Nasution, Nurul Putri Awaliah; Jubair , Jubair; Wahid , Abdul (Rechtsidee, 2022)
The criminal justice system is a comprehensive effort by the state to tackle crime and determine accountability for each offense. In this case, the criminal justice system also emphasizes the importance of non-prison efforts to determine crime responsibility, commonly referred to as restorative justice. This study aims to describe the application of the concept of restorative justice in other countries and the orientation of its application in Indonesia. This research is normative legal research. Normative legal research is oriented toward answering legal issues and finding prescriptions for a legal problem. This study uses a statutory procedure, a concept approach, and a comparative approach. The results of the study confirm that the concept of restorative justice is part of the development of world law which is applied in various countries with different legal systems, such as the Netherlands, the United States, and Malaysia. In addition, the concept of restorative justice also needs special arrangements in the Criminal Procedure Code to reform the criminal procedure law in Indonesia.